ANALISIS KEPUASAN ORANG TUA TERHADAP PEMBELAJARAN DARING SELAMA MASA PANDEMI COVID -19 - Nourma Yunita; Lidia Aditama Putri (Jurnal Muara Pendidikan, 2021)
The spread of the corona virus in various countries has made major changes, such as the economy, technology and education is no exception. The Covid-19 pandemic has forced social distancing policies. The central and regional governments issue policies to close all educational institutions. The lockdown or quarantine policy is carried out as an effort to reduce interaction with many people who can give access to the spread of the virus. The study from home policy means that learning must be carried out online. This study was conducted with the aim of knowing the Analysis of Parental Guardian Satisfaction with Online Learning During the Covid-19 Pandemic Period at Ra Al-Akbar Surabaya. The research method is a quantitative approach and the type of research is descriptive. The population of this study was the guardians of the students of RA Al-Akbar Surabaya as many as 165. The sample was taken using a random sampling system, namely random sampling so that a sample of 131 people was obtained. Data collection techniques with google form. The data analysis technique uses analysis by mapping the frequency distribution on aspects of satisfaction. The results of this study have an average value of student guardian satisfaction with online learning during the covid-19 pandemic at RA Al-Akbar Surabaya is 52.85%. The average level of reality assessment of online learning services during the covid pandemic is 2.04 (Sufficient Satisfactory) while the expectation level is 3.86 (Important).The conclusion of this study is that more than 50% of the guardians of students at RA Al-Akbar Surabaya are satisfied with online learning during the covid pandemic pandemic.